Efektivitas Antioksidan Angkak terhadap Performans Burung Puyuh yang Diinduksi Stres Oksidatif dengan Pemberian Deksametason - Ardiani, Nuri; Santoso, Koekoeh; Maheshwari, Hera (Jurnal Veteriner, 2019)
Red yeast rice is a fermented product of rice and mold Monascus purpureus. Red yeast rice contains secondary metabolites such as lovastatin, phenol and flavonoids that have potential as antioxidants. This study was aimed to examine the effectiveness of red yeast rice antioxidants on performance of japanese quail administered with dexamethasone through the parameters of feed digestibility, feed consumption, growth in body weight, stress index, malondialdehyde (MDA) andsuperoxide dismutase (SOD). This study used a factorial completely randomized design. The animals used in this study were 60 quails (Coturnix coturnix japonica), with a body weight of 140195 grams.  Group K0 was a control, group D were quails given only dexamethasone at a dose of 1.25 mg/g BW for 7 days after one-week adaptation. Group D+VC were quails given dexamethasone at a dose of 1.25 mg/g BW then added with vitamin C at a dose of 20 mg. Group D+K1, D+K2, and D+K3 were quails given dexamethasone then orally given red yeast rice of 18 mg, 24 mg, and 30 mg for 14 days. The feed consumption, feed digestibility and body weight shows no significant difference among group (P>0.05). The heterophyl/lympocyte ratio was elevated when dexametasone administered and tended to decrease when administered with red yeast rice. Result also showed that red yeast rice has the potential as an antioxidant in quail administered with dexamethasone as seen from the tendency of decreased level of MDA and increased level of SOD enzyme. The results also showed that quail administered with dexamethasone decreased level of MDA and elevated levels of SOD enzyme in the liver after administration of red yeast rice.
Keywords: antioxidant, dexamethasone, red yeast rice